The Effectiveness of Education to Increase Motivation and Primary Cervical Cancer Prevention Actions - Surinati, I Dewa Ayu Ketut; Widjanegara, I Gede; Suratiah, Suratiah; Ribek, Nym (LPPM Undiksha, 2020)
Cervical cancer is a type of malignancy found among women, with the second highest number of sufferers globally aged 15 to 44. However, the motivation for women to do cervical cancer prevention is still low. This study aimed to test the effectiveness of education on motivation and primary prevention measures for cervical cancer in young women. The research method used was an experimental design with a pre-test post-test control group design. The sampling technique used was a proportional random sampling of 150 respondents who met the inclusion criteria, 75 as the experimental group, and 75 as the control group. The statistical test used was Wilcoxon and Mann Whitney test. The Wilcoxon test results showed that the p score was 0.000 <0.05, which means a significant difference in motivation and action in the experimental and control groups before and after education. Test results. Mann Whitney showed a p score was 0.000 <0.05. Based on these results, it can be concluded that education effectively increases motivation and the primary prevention of cervical cancer.